Marketing Agility: The Concept, Antecedents, and a Research Agenda - Kalaignanam, Kartik; Tuli, Kapil R.; Kushwaha, Tarun; Lee, Leonard; Gal, David (Journal of Marketing, 2021)
Changes in the way customers shop, accompanied by an explosion of customer touchpoints and fast-changing competitive and technological dynamics, have led to an increased emphasis on agile marketing. The objective of this article is to conceptualize and investigate the emerging concept of marketing agility. The authors synthesize the literature from marketing and allied disciplines and insights from in-depth interviews with 22 senior managers. Marketing agility is defined as the extent to which an entity rapidly iterates between making sense of the market and executing marketing decisions to adapt to the market. It is conceptualized as occurring across different organizational levels and shown to be distinct from related concepts in marketing and allied fields. The authors highlight the firm challenges in executing marketing agility, including ensuring brand consistency, scaling agility across the marketing ecosystem, managing data privacy concerns, pursuing marketing agility as a fad, and hiring marketing leaders. The authors identify the antecedents of marketing agility at the organizational, team, marketing leadership, and employee levels and provide a roadmap for future research. The authors caution that marketing agility may not be well-suited for all firms and all marketing activities.